STIM2 promotes the invasion and metastasis of breast cancer cells through the NFAT1/TGF-β1 pathway - Cheng, Hongbing; Chen, Liangji; Fang, Zhenyu; Wan, Qian; Du, Zhuo; Ma, Nanshan; Guo, Genxin; Lu, Wenjing (Cellular and Molecular Biology, 2022)
A large amount of evidence indicates that the abnormal activation of multiple signal transduction pathways in cells is closely related to the occurrence and development of tumors. TGF-β and NFAT1 signaling pathways can inhibit cell proliferation and promote apoptosis in the early stage of breast cancer, but with the increase of tumor malignancy, the two appear to promote tumor progression and deterioration. Therefore, the study of the relationship between STIM2 and NFAT1/TGF-β1 is helpful for the discovery and treatment of breast cancer, which is of great significance for improving the survival rate of breast cancer patients. This article focuses on the effect of STIM2 molecules on breast cancer cell migration through the NFAT1/ TGF-β1 pathway and discusses the regulatory mechanism of STIM2 affecting breast cancer cell migration. Experimental data shows that the positive rate of breast cancer NFAT1 is 54%, which is significantly lower than that of benign breast Tissue 85%; the positive expression rate of TGF-β1 in benign breast tissue is 85%, and the positive expression rate in breast cancer tissue is 49%. The results show that STIM2 protein can promote the invasion and metastasis of breast cancer cells through the NFAT1 / TGF-β1 pathway.